Nutrition Modification in the COVID-19 Quarantine Process: Focus on Sleep Alteration, Anxiety and Happiness Factors - Sabiha Gökçen Zeybek; Gonca İnanç; Adile Öniz; Murat Özgören (Türk Uyku Tıbbı Dergisi, 2022)

(untitled)
Objective:Coronavirus disease-2019 pandemic has made the quarantine process essential to protect public health and prevent the risk. The aim of this study was to evaluate the effect of the quarantine process applied in Turkish speaking population on nutritional changes. Additionally, the relationship between nutritional and sleep pattern changes, anxiety and happiness status was evaluated.Materials and Methods:A questionnaire form was applied via the Google Forms application. General information was questioned with a socio-demographic form. Changes in nutrition and sleep patterns were obtained with closed-ended questions asked using the self-assessment method, and the levels of anxiety and happiness were obtained using the Likert-type question technique.Results:Total of 900 people who completed the questionnaire were included. Almost half of the participants reported that they experienced nutritional changes and 54.1% did not. Also, it was determined that females experienced more than males (p≤0.001). Participants reported that the quarantine process also caused sleep pattern changes. However, nutritional changes were also found to be significantly higher in participants who experienced sleep pattern changes. It was shown that increased happiness and anxiety levels were associated with nutritional changes (p≤0.001). Regardless of nutrition, sleep pattern changes were more common who reported high anxiety and better happiness status (p≤0.001). It was found that females had more sleep problems than males during the quarantine period (p=0.006).Conclusion:People responsible for public health should be aware of crisis processes such as quarantine may cause short and/or longterm health problems in public health and should try increasing social and individual awareness.